Implementation of Complex Propotional Assesment (COPRAS) in Determining Air Conditioning System Traders - Idaman, Akbar; Amrullah, Amrullah; Raja Gunung, Tar Muhammad; Eldo, Handry; Prabowo, Agung (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2024)
Increased global warming and awareness of the need to reduce greenhouse gas emissions have strengthened the focus on energy efficiency in various sectors, including the HVAC (Heating, Ventilation, and Air Conditioning) industry. In this context, the selection of air conditioning (AC) systems becomes crucial in providing thermal comfort. However, decisions regarding air conditioning systems are often complex as they involve considerations of energy efficiency, operational costs, system reliability, and environmental impact. To address this complexity, Complex Proportional Assessment (COPRAS) emerged as an effective multi-criteria analysis method. However, the application of COPRAS in determining AC system traffickers is still limited. This research explores the possible application of COPRAS in this context and identifies key factors to consider. The evaluation results show that Medan Elektronik and Citra Inovasi Prima are the top choices in the selection of AC system traffickers. This research is expected to contribute to the development of more sophisticated analysis methods in the HVAC industry as well as assist decision makers in selecting more appropriate and sustainable air conditioning systems.